Prime ideal on the end_Z (Z^n ) Ring - Ikhtiyar, Zakaria Bani; Puspita, Nikken Prima; Udjiani, Titi (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
The set of all endomorphisms over -module is a non-empty set denoted by . From we can construct the ring of over addition and composition function. The prime ideal is an ideal which satisfies the properties like the prime numbers. In this paper, we take the ring of integer number and the module of over such that the is a ring. Furthermore, we show the existences of prime ideal on the . We also applied a prime ideal property to prime ideal on .